Enhanced dielectric, ferroelectric and magnetic properties of Ba4Sm2Fe2Nb8O30 RT multiferroics prepared by microwave sintering. Issue 15 (1st August 2021) - Huang, X.; Liu, Y.T.; Luo, G.S.; Lin, C.; Wu, X.; Zheng, X.H.; Tang, D.P.
Abstract: High density Ba4 Sm2 Fe2 Nb8 O30 (BSFN) multiferroics ceramics with tetragonal tungsten bronze structure had been prepared by microwave sintering (MS) for 30min and conventional sintering (CS) methods for 4 h at 1275 °C. Single tungsten bronze phase and equiaxial grains are obtained for the MS BSFN ceramics, while a small amount secondary phase of SmNbO4 is observed in the CS BSFN ceramics with columnar grains. Compared to Ba4 Sm2 Fe2 Nb8 O30 ceramics prepared by CS method, enhanced dielectric, ferroelectric and magnetic properties are achieved for the MS BSFN ceramics. The values of electric polarization Pr and coercive electric field Ec are 2.11 μC/cm 2 and 7.14 kV/cm for the MS BSFN ceramics, respectively. Meantime, the magnetic polarization Mr of 0.410emu/g and coercive magnetic field Hc of 2930Oe are also obtained for the MS BSFN ceramics. Based on the density, crystal structure, point defect and grain, the reasons of enhanced dielectric, ferroelectric and magnetic properties are discussed for the MS BSFN ceramics It is indicated that Ba4 Sm2 Fe2 Nb8 O30 is an intrinsic room temperature multiferroic materials.